“On A Mission”: Preserving Creole Culture One Tweet at a Time. Keith Frank, Zydeco, and the Use of Social Media - Marie Demars (Transatlantica)
Appearing approximately sixty years ago among the Creole community of urban Houston, zydeco is a relatively new musical genre that is however still associated to rurality, folklore and old-fashioned ways. In this unfavorable context, it might seem difficult to link zydeco with modernity or high-profile communication tools and technologies, yet more and more young Creole musicians are bridging the gap by heavily using social media to promote their music as well as their south Louisiana cultural heritage.